Effects of 12 weeks high-intensity & reduced-volume training in elite athletes - Kilen, A.; Hultengren Larsson, T.; Jørgensen, M.; Johansen, L.; Jørgensen, S.; Nordsborg, N. B. (PLOS ONE, 2014)
It was investigated if high-intensity interval training (HIT) at the expense of total training volume improves performance, maximal oxygen uptake and swimming economy. 41 elite swimmers were randomly allocated to a control (CON) or HIT group. For 12 weeks both groups trained ~12 h per week. HIT comprised ~5 h vs. 1 h and total distance was ~17 km vs. 35 km per week for HIT and CON, respectively. HIT was performed as 6-10×10-30 s maximal effort interspersed by 2-4 minutes of rest. Performance of 100 m all-out freestyle and 200 m freestyle was similar before and after the intervention in both HIT (60.4±4.0 vs. 60.3±4.0 s; n = 13 and 133.2±6.4 vs. 132.6±7.7 s; n = 14) and CON (60.2±3.7 vs. 60.6±3.8 s; n = 15 and 133.5±7.0 vs. 133.3±7.6 s; n = 15). Maximal oxygen uptake during swimming was similar before and after the intervention in both the HIT (4.0±0.9 vs. 3.8±1.0 l O2×min-1; n = 14) and CON (3.8±0.7 vs. 3.8±0.7 l O2/min; n = 11) group. Oxygen uptake determined at fixed submaximal speed was not significantly affected in either group by the intervention. Body fat % tended to increase (P = 0.09) in the HIT group (15.4±1.6% vs. 16.3±1.6%; P = 0.09; n = 16) and increased (P<0.05) in the CON group (13.9±1.5% vs. 14.9±1.5%; n = 17). A distance reduction of 50% and a more than doubled HIT amount for 12 weeks did neither improve nor compromise performance or physiological capacity in elite swimmers.